Nifedipine-cyclodextrin binary systems : solid-state photostability and dissolution behaviour - Worthington, Matthew Stanley (Rhodes University, Faculty of Pharmacy, Pharmacy, 1998)
Nifedipine is a photolabile calcium channel antagonist which undergoes rapid photodegradation in solution and in solid-state with an accompanying loss of pharmacological potency and clinical efficacy. Nifedipine photostabilization which has received considerable attention has principally been achieved by physical obscuration and through the use of colourants or ultraviolet light absorbers incorporated into liquid preparations, translucent packaging materials, gelatin capsules and/or their fillings and tablet coatings or cores. This study was initiated by a South African pharmaceutical manufacturer in response to increasing evidence that cyclodextrin (CD) inclusion complexation may improve drug photostability. The brief was to evaluate the potential of selected cyclodextrins as photoprotecting agents for nifedipine in the solid-state. Areas of investigation included i) quantitative method development and validation for selective determination of nifedipine, ii) phase solubility studies to establish the solubilizing potential and complexing tendencies of selected cyclodextrins, iii) preparation of solid-state nifedipine - cyclodextrin binary systems using an industrially applicable method, iv) pre-formulation photostability studies to determine the effects of the cyclodextrins on solid-state nifedipine photostability and v) comparative in vitro dissolution assessments of nifedipine, the nifedipine - cyclodextrin binary systems and their respective physical mixtures. Phase solubility studies demonstrated that soluble nifedipine - cyclodextrin complexes were formed in aqueous solution, but the magnitude of the interactions were generally low as reflected by the calculated stability constants which decreased in the rank order, heptakis (2,6-dimethyI)-Î²-CD (DM-Î²-CD) > randomly methylated-Î²-CD (RM-Î²-CD) > Î²-CD â‰ˆ 2-hydroxypropyl-Î²-CD (2HP-Î²- CD) > Î³-CD â‰¥ 2-hydroxypropyl-Î³-CD (2HP-Î³-CD). An industrially applicable kneading method yielded binary systems with spectral and thermal characteristics similar to the respective physical mixtures, implying weak solid-state inclusion complexation. Preparation of an amorphous nifedipine - RM-Î²-CD product using a heating method is reported. A 1.7- and 1.9-fold improvement in solid-state nifedipine photostability was observed for I : 1 molar ratio Î²-CD and Î³-CD kneaded products, respectively, when exposed to window-filtered daylight and could be attributed to changes in opacity of the crystalline kneaded products. The remaining cyclodextrins produced negligible nifedipine photostabilization. Nifedipine in vitro dissolution was improved considerably from Î³-CD and RM-Î²-CD .kneaded products as a result of increased nifedipine wettability, solubility and reduced particle size. iii
Keywords: Nifedipine; Calcium -- Antagonists; Cyclodextrins; Cyclodextrins in pharmaceutical technology